Community Strategy in Economic Improvement Based on the Utilization of Perlis Marine Natural Resources - Rahmadani, Kartini; Putra, Ilham Mirzaya (LP2M INSURI Ponorogo, 2024)
The Perlis village is an oceanside community with abundant marine natural resources. However, the local economy needs to be better structured, contributing to the village's reputation as impoverished and undeveloped. As a result, the village's fishermen earn very little money, which is a shame because the village should be considered prosperous, particularly in the fishing industry. The researchers in this study set out to answer two questions: how can the people of Perlis Village enhance their economy? And second, what steps can they take to protect the sea and its marine biota so that they can use it to their advantage? They used a descriptive qualitative research approach to answer these questions and scoured academic journals, books, statistics, and BPS Langkat Regency for information. They then conducted in-depth interviews and observations with five fishermen and three UMKM seafood representatives. Data analysis by description to understand the field's, market's, and village's status; data validity through source triangulation through comparison with other sources. Based on the findings, the people of Perlis Village have improved their economic situation by implementing strategies that use marine products. These include increasing their fish catches, turning seawater into salt, creating shrimp paste artisans, making salted fish from unsold fish, and managing mangrove tourism. The plan implemented by the residents of Perlis Village has the potential to enhance the economic situation in Perlis Village.